Expanded of Informal Jobs in Iranian Border Cities, Case: Zabol-Iran - Bazzi, Khodarahm (International Journal of Geography and Geology, 2015)
Informal jobs is the part of an economy that is not taxed, monitored by any form of government, or included in any gross national product (GNP), unlike the formal economy. The growing popularity of the informal jobs (especially peddler) in cities is to be found in both hidden and obvious mechanisms rooted in unorganized in the formal sector. What makes issues difference between informal jobs in Zabol rather other cities of Iran are located Zabol in near of Afghanistan borders. So that the phenomenon of smuggling and illegal enter of Afghans to Iran expanded this problem in Sistan region and Zabol city. With attention to multidimensional of subject, in this paper has been used of analytical- description methods and survey activities to understand of peddlers jobs and distribution of questionnaire in both single and mixed status. Also for access to statistical data’s has been used of Zabol municipality reports. Results show that status border of Sistan region and some related works to it (such as: smuggling and resident of illegal Afghans) led to expanded of informal jobs in Zabol city.